Tattoos in the general Swedish population: prevalence, determinants, and exposure characteristics - Nielsen, Christel ; 0000-0003-3940-7847; Saxne Jöud, Anna ; 0000-0001-7192-4911 (European Journal of Public Health, 2025)
Tattoo ink on the European market has been reported to contain many human toxicants, which has raised concerns about health effects. Clarifying the exposure distribution in the population is key to understanding potential public health implications. We investigated the prevalence of tattoos in a population-based Swedish cohort of 13 046 individuals aged 20–68 years with exposure data collected through a questionnaire in 2021. In addition, we characterized the tattooed population in terms of sociodemographic and socioeconomic determinants and exposure characteristics using multivariable logistic regression, regressing tattoo status on sex, age, educational attainment, marital status, smoking, snuff use, and alcohol consumption. The age-standardized tattoo prevalence was estimated at 29% (95% confidence interval [CI] 27%–30%). Tattoos were more common in the younger age groups, particularly among females. Males were younger when they received their first tattoo and tended to have a larger tattooed body surface. Tattoo exposure was associated with unfavourable socioeconomic characteristics, with the highest odds ratio observed for current smokers compared with never-smokers (2.86; 95% CI 2.42–3.38). Our results suggest that any tattoo-related adverse effects may exacerbate existing inequalities in health. Additionally, the high prevalence in younger age groups indicates a likely shift in the characteristics of the tattooed population over time, which may have further implications for public health.
Keywords: Tattoo; Determinants; Population Exposure